EXPANDED SELECTING CRITERIA OF RESEARCH DATABASES FOR UNIVERSITY LIBRARIES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Access to valuable scientific and educational resources is an important aspect of the effectiveness of the educational process. Depending on their financial capabilities, academic libraries subscribe to various databases of the world's leading publishers. It is very important to evaluate certain databases in order to select the necessary sources of information for educational and scientific activities. The purpose of the article is to determine the most important criteria for evaluating scientific and educational databases in academic libraries based on a survey conducted among teachers and students of technical universities of the Republic of Uzbekistan.  The key criteria are content relevance, thematic coverage, usability, accessibility, technical specifications, licensing models, and scalability to meet future needs. The study emphasizes the importance of aligning database selection with institutional research priorities, user accessibility requirements, and emerging fields of study. Additionally, the role of open-access resources, interdisciplinary content, and vendor support in decision-making is analyzed. By developing a comprehensive framework for database evaluation, this article provides valuable insights for librarians and academic institutions seeking to optimize their resource offerings and support diverse research endeavors.